Benzophenone-3, a chemical UV-filter in cosmetics: is it really safe for children and pregnant women? - Wnuk, Weronika; Michalska, Klaudia; Krupa, Anna; Pawlak, Krystyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Children and adolescents are particularly vulnerable to skin damage caused by ultraviolet radiation and require intensified photoprotection. Benzophenone-3 (BP-3) belongs to the organic sunscreens, which are widely used in personal care and cosmetic products. However, the impact of BP-3 on human health requires a careful assessment. This review focuses on potentially harmful effect of this compound in relation to the developing organism. Studies show that BP-3, after topical application, can penetrate into bloodstream, blood-brain barrier and blood-placental barrier and may induce the reproductive toxicity and abnormal development of the foetus, endocrine system disruption and neurotoxicity in experimental animal models. So far, human studies have been scarce and controversial, therefore the cosmetics containing BP-3 should be carefully used by the pregnant women, children and adolescents.